PEMBERDAYAAN KELOMPOK TANI UNTUK PERSIAPAN BAHAN BAKU INDUSTRI NANAS (Ananas comosus (L) Merr.) DI KECAMATAN NGANCAR DAN PLOSOKLATEN KABUPATEN KEDIRI - Suryanto, Agus; Sitawati, .; Noor, Arifin; Nurlaelih, Euis Elih; Damaiyanti, D. R. R. (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The community service aims to empower the pineapple farmers (Ananas comosus L.) in Ngancar and Plosoklaten Districts, Kediri Regency, by improving cultivation technology to produce higher quality fresh fruit and diversifying post-harvest products to add various marketable products. Farmers need for pineapple seeds that have not been met and improper plant cultivation technology were some of problems faced by farmers in this area. In addition, superior varieties developed are still limited, hence choices in improving quality are limited. Farmers limited knowledge on the post-harvest technology in pineapple cultivation has caused the farmers have no other choice but to market their products only in the form of fresh fruit. Part of the plant which is prioritized for production was only the fruit, there has not been any innovation in utilizing other plant parts such as pineapple leaves as raw material for pineapple fiber industry. In this community service, counseling has been successfully conducted on the selection of pineapple seedlings and superior varieties, improvement of pineapple plant maintenance and Plant Growth-Promoting Rhizobacteria (PGPR). Implementation of community service started with socialization and counseling on the selection of pineapple seedlings and superior varieties, improvement of pineapple plant maintenance and PGPR. In addition, practice and assistance were carried out in the characterization and selection of superior varieties of pineapple seedlings. The result obtained is that the partner community is able to apply pineapple plant cultivation technology in an integrated manner. Keywords: Pineapple, extension, seeds, superior varieties. ABSTRAK Tujuan pengabdian masyarakat adalah pemberdayaan kelompok tani Langgeng Mulyo nanas (Ananas comosus L.) di Kecamatan Ngancar dan Plosoklaten, Kabupaten Kediri dengan cara perbaikan teknologi budidaya untuk menghasilkan buah segar yang lebih berkualitas dan diversifikasi produk pasca panen untuk menambah berbagai produk yang bisa dipasarkan. Permasalahan pada Kelompok Tani di Kecamatan Ngancar dan Kecamatan Plosoklaten, Kabupaten Kediri, antara lain adalah kebutuhan bibit nanas yang belum dapat dipenuhi dan teknologi budidaya tanaman nanas yang kurang tepat. Varietas unggul yang dikembangkan masih terbatas sehingga pilihan dalam perbaikan kualitas menjadi terbatas. Keterbatasan pengetahuan tentang teknologi pasca panen pada pelaku budidaya nanas menyebabkan pelaku budidaya tidak mempunyai pilihan lain selain memasarkan produk hanya dalam bentuk buah segar. Bagian tanaman yang diutamakan produksinya hanya pada bagian buah, belum terdapat inovasi memanfaatkan bagian tanaman yang lain seperti daun nanas sebagai bahan baku industri serat nanas. Pada pengabdian ini telah berhasil dilakukan penyuluhan mengenai seleksi bibit nanas dan varietas unggul, perbaikan pemeliharaan tanaman nanas dan Plant Growth Promoting Rhizobacter (PGPR). Pelaksanaan pengabdian masyarakat dilakukan diawali dengan sosialisasi dan penyuluhan tentang seleksi bibit nanas dan varietas unggul, perbaikan pemeliharaan tanaman nanas dan PGPR. Selain itu dilakukan praktek dan pendampingan dalam karakterisasi dan seleksi bibit nanas varietas unggul. Hasil yang diperoleh adalah masyarakat mitra mampu menerapkan teknologi budidaya tanaman nanas secara terpadu. Kata kunci: Nanas, penyuluhan, bibit, varietas unggul.